Evolution of Naturally Dried MXene-Based Composite Aerogels with Flash Joule Annealing for Large-Scale Production of Highly Sensitive Customized Sensors - Zhu, Wenqi (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.